PENELITIAN UPAYA PENINGKATAN KUALITAS PRODUK TEKSTIL DAN GARMEN JAWA TENGAH MEMASUKI PASAR GLOBAL - Mursid Zuhri (JURNAL LITBANG PROVINSI JAWA TENGAH, 2004)
Textile and garment's industry Century, has bicome lead industry atcommodity out of various varions area in Central Java. Nowadays textile and garment's industry still become the main non oil and gas industry which produce export's foreign exchange. The governmentshould maintain this industry as well as priority. With the implementation of AFTA 2003, the competition between textile product and garment become more thight; which the product within theASEAN area competitive freely. Cenral Java's Textile and garment product besides compete with theASEAN's product, also compete with big textile and garment country producers, such as China, Hongkong and India. The main key in the competition is textile and garment product quality to fulfall the domestic market and international quality standard. In improving the textile and garment quality in Central Java entering the A PTA 2003, it is recommended that in order to improve the competitive capacity based on comparative and competitive local capacity and market oriented, using united quality manajemen, international standardization and sertification, and using technology and manajemen in market regulation which back-upthe market mechanism.